2021
DOI: 10.1101/2021.07.12.451780
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Experimental evolution of Vibrio cholerae: Identification of genes involved in motility in presence of polymyxin B

Abstract: Vibrio cholerae is the bacteria responsible for the cholera disease and a natural inhabitant of aquatic environments. Biofilm formation is important for human colonization and environmental survival. Motility is essential for adhesion and biofilm formation by V. cholerae. In a previous study, we showed that motility and biofilm formation are altered in the presence of sub-inhibitory concentrations of polymyxin B in V. cholerae. In this study, we performed an experimental evolution to identify genes rescuing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…We observed a difference in resistance to PmB, for which a 3-fold increase in the CI50 is observed under anaerobic conditions compared to aerobiosis. The main mechanisms of PmB resistance in V. cholerae involve alterations in LPS and vesicle production (29,37,38). A recent study demonstrated LPS modification under anaerobic conditions in V. cholerae when grown in a TMAO-and bile-enriched medium (39).…”
Section: Discussionmentioning
confidence: 99%
“…We observed a difference in resistance to PmB, for which a 3-fold increase in the CI50 is observed under anaerobic conditions compared to aerobiosis. The main mechanisms of PmB resistance in V. cholerae involve alterations in LPS and vesicle production (29,37,38). A recent study demonstrated LPS modification under anaerobic conditions in V. cholerae when grown in a TMAO-and bile-enriched medium (39).…”
Section: Discussionmentioning
confidence: 99%